Residual polycyclic aromatic hydrocarbons and firefighters' hematological profile - Zhu, Mingze; Agnew, Robert J.; Xu, Chao; VanWagoner, Timothy; Xu, Xin; Hwang, Jooyeon (Frontiers in Environmental Health, 2024)
Introduction Firefighters are exposed to polycyclic aromatic hydrocarbons (PAHs) during fire suppression, but the extent of PAH penetration through turnout gear and its impact on blood cell components remains uncertain. The main objective of this study is to investigate the residual levels of PAHs on turnout gear and skin, and to assess their potential effects on blood cell components in firefighters. We hypothesize that firefighting activities lead to increased PAH exposure, which in turn may induce alterations in blood cell composition. We also hypothesize that differences in PAH exposure and corresponding blood cell changes will be observed between volunteer and career firefighters. Methods Forty-seven firefighters were recruited from 11 fire departments in Oklahoma. PAH levels on gear and skin were measured, and complete blood count (CBC) parameters were analyzed. Parametric and non-parametric tests were used to examine differences in PAH exposures and hematological profiles between volunteer and career firefighters and possible changes over time. Generalized estimating equation (GEE) models were performed to assess the relationships between PAHs and blood cells. Results Our analysis revealed significant hematological differences between volunteer and career firefighters, with volunteers exhibiting lower aerobic capacity and higher systemic inflammation. Increased levels of specific PAHs were found on volunteers' gear post-fire. Conclusion Our findings indicate an association between PAH exposure and changes in blood parameters, emphasizing the need for improved decontamination protocols and protective measures, particularly for volunteer firefighters.